2010
DOI: 10.1111/j.1526-4637.2010.00877.x
|View full text |Cite
|
Sign up to set email alerts
|

Post-marketing Surveillance of Methadone and Buprenorphine in the United States

Abstract: Buprenorphine appears to have a better safety profile than methadone during routine outpatient medical use. However, both medications have roles in the treatment of pain and opioid addiction, and further research into their respective benefits and risks should be conducted.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
59
1

Year Published

2012
2012
2018
2018

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 72 publications
(62 citation statements)
references
References 71 publications
2
59
1
Order By: Relevance
“…• Health Canada exemption is not required to prescribe buprenorphine-naloxone in most provinces and territories (Appendix 1) • Lower risk of overdose due to partial agonist properties and ceiling effect for respiratory depression (in the absence of benzodiazepines or alcohol) 19,24,25 • Lower risk of public safety harms if diverted 26,27 • Milder adverse effect profile 22,23 • Easier to transition from buprenorphine-naloxone to methadone if treatment is unsuccessful 22,23 • Shorter time to achieve therapeutic dose (1-3 d) [28][29][30] • Lower risk of toxicity and drug-drug interactions 31 • Milder withdrawal symptoms when discontinuing treatment; may be a better option for individuals with lower-intensity opioid dependence (e.g., oral opioid dependence, infrequent or no injection use, short history of opioid use disorder), and individuals planning to taper off opioid agonist treatment in a relatively short period 22,23 • Optimal for rural and remote locations where access to care is limited, methadone prescribers are lacking, or daily witnessed ingestion at a pharmacy is not feasible • More flexible dosing schedules (e.g., alternate-day dosing, earlier provision of 1-to 2-week take-home prescriptions, and unobserved home inductions) support patient autonomy and can reduce costs [32][33][34][35] • Easier to adjust and retitrate following missed doses, owing to its partial agonist properties…”
Section: Drug-drug Interactions and Adverse Eventsmentioning
confidence: 99%
“…• Health Canada exemption is not required to prescribe buprenorphine-naloxone in most provinces and territories (Appendix 1) • Lower risk of overdose due to partial agonist properties and ceiling effect for respiratory depression (in the absence of benzodiazepines or alcohol) 19,24,25 • Lower risk of public safety harms if diverted 26,27 • Milder adverse effect profile 22,23 • Easier to transition from buprenorphine-naloxone to methadone if treatment is unsuccessful 22,23 • Shorter time to achieve therapeutic dose (1-3 d) [28][29][30] • Lower risk of toxicity and drug-drug interactions 31 • Milder withdrawal symptoms when discontinuing treatment; may be a better option for individuals with lower-intensity opioid dependence (e.g., oral opioid dependence, infrequent or no injection use, short history of opioid use disorder), and individuals planning to taper off opioid agonist treatment in a relatively short period 22,23 • Optimal for rural and remote locations where access to care is limited, methadone prescribers are lacking, or daily witnessed ingestion at a pharmacy is not feasible • More flexible dosing schedules (e.g., alternate-day dosing, earlier provision of 1-to 2-week take-home prescriptions, and unobserved home inductions) support patient autonomy and can reduce costs [32][33][34][35] • Easier to adjust and retitrate following missed doses, owing to its partial agonist properties…”
Section: Drug-drug Interactions and Adverse Eventsmentioning
confidence: 99%
“…However, an American study on the Researched Abuse Diversion and Addiction-Related Surveillance (RADARS) System Program reports 314 calls to Poison Centers between 2003 and 2007 (4% of all calls) in which both liquid and tablet methadone were ingested. [28] Several explanations are possible. The two formulations could be used by the patient, or one of them could be used by someone else, stored or even sold on the black market.…”
Section: Discussionmentioning
confidence: 99%
“…A US post-marketing surveillance study on methadone and buprenorphine found that between 2003 and 2007, rates of abuse, misuse, and diversion of both compounds increased steadily [83]. Rate ratios (per 100,000 population per quarter) of abuse, misuse, and diversion were consistently higher for methadone than buprenorphine.…”
Section: Extent Of the Problem In The Us And Non-european Countriesmentioning
confidence: 99%